Religious rivalries and the struggle for success in Sardis and Smyrna - Ascough, Richard S. (Studies in Christianity and Judaism ;, 2005)
This volume, one in a series of books examining religious rivalries, focuses in detail on the religious dimension of life in two particular Roman cities: Sardis and Smyrna. The essays explore the relationships and rivalries among Jews, Christians, and various Greco-Roman religious groups from the second century bce to the fourth century ce. The thirteen contributors, including seasoned scholars and promising newcomers, bring fresh perspectives on religious life in antiquity. They draw upon a wide range of archaeological, epigraphic, and literary data to investigate the complex web of relati.